Concentrating Solar Thermal Energy Storage Using Amide-Hydride Systems - Nguyen, Tam Thanh (Curtin University, 2017)
Amide-hydride systems can be used in thermal storage systems by taking advantage of their endothermic/exothermic reactions with hydrogen. This allows the harnessing of concentrated solar energy by utilising thermal storage to alleviate its intermittent nature. Amide-hydride reactions have been widely studied for their low temperature applications. However, the high temperature imide-hydride reactions are more suitable for thermal energy storage. Lithium, magnesium and calcium-based amide-imide-hydride systems were investigated with potential candidates from systems containing calcium metal.